3. A SURVEY OF HYPOTHESES FOR THE 100-KYR CYCLE - Claussen M.; Berger A.; Held H. (My University, 2007)
Theories and mathematical models of longterm Quaternary climate variations are briefly summarized and revisited. We conclude that the problem of Quaternary climate variations, in particular the existence of a dominant 100-kyr ice-age cycle is, even approximately 160 years after first geological evidence of ice ages was found, not yet solved. However, we have some clues on what elements a theory of Quaternary Earth system dynamics should consist of. Assessment of a number of conceptual models —ranging from models in which forcing is necessary to yield observed climate variability to models of free climate oscillations — cannot favour any model over its competitor on the grounds of tuning each model to the time series of global ice volume. Hence, geographically explicit fully coupled climate system, or natural Earth system, models are required to analyse the system's response to geographically varying forcing and internal feedbacks. Evidence emerges that much of Quaternary climate variability arises due to internal feedbacks, with ice sheets and biogeochemical cycles as critical elements and orbital forcing as pacemaker.
Keywords: Cenozoic::Quaternary; Кайнозой::Четвертичная